Search and location of body deposition sites: the role of winthropping and other innovative approaches - Conway-Grim, Tanja (Cranfield University, 2019)
Homicide is regarded as one of the gravest of all crimes, and those cases where the body is initially missing are more difficult to solve, partly due to a potential loss of forensic evidence. This research investigated the potential role of winthropping (a counter-terrorism search technique developed by the British Army in Northern Ireland), tracking, wayfinding and lowland search and rescue techniques in the search for and location of rural body deposition sites. The focus was on ‘no body’ murders due to their high impact on society, and the people left behind having to deal with the ambiguous loss of their loved ones. Appropriate search training with the police, Lowland Rescue and military trackers was undertaken. Search professionals from within the police, military, lowland rescue and search organisations were interviewed. Specific distance data (known as track offset distance) of body deposition sites and locations where missing suicidal males were found, were compared to see whether their search parameters were similar. Training differences were noted especially relating to navigation and map reading. Most interviewees were familiar with winthropping, but few had applied its principles to the search and location of body deposition sites. ‘Fault lines’ surfaced as an (unexpected) topic, specifically: communication, financial constraints, statistics, rank and tasking. Homicide was seen as rare and complex, with accurate, intelligence-led tasking being a priority. The use of outside agencies (such as man-trackers and Lowland Rescue) seemed very much dependent upon the police search professional’s personal preference and experience, rather than a consistent national evidence-based approach.